Factors Influencing the Distribution of Community Libraries in China: A Systematic Literature Review - Yaping, Chen; Rawai, Norshakila Muhamad; Lai, Khoo Sui (Journal of Ecohumanism, 2025)
Community libraries, as an integral part of community culture, play a key role in collecting and providing knowledge and information for residents. Their distribution directly affects the equity and convenience of services. However, the rational distribution of community libraries is influenced by a combination of factors, but there is a small body of literature on the impact of the distribution of community libraries, and the literature covers an incomplete range of influencing factors. This study systematically collects and analyses relevant literature to identify the key factors affecting the distribution of community libraries, encompassing five main aspects: population, transportation, economy, environment, and policy. The research aims to determine the factors that influence the distribution of community libraries in China. The research methodology applied in this study is a systematic literature review comprising 15 indexed journals. The integration of the existing literature is expected to provide theoretical support for the next research.